The Compatibility of a GIS Map of Landslide-Prone Areas in Kendari City Southeast Sulawesi with Actual Site Conditions - Andri Estining Sejati; Ahmad Tarmizi Abd Karim; Akbar Tanjung (Forum Geografi, 2020)
Kendari is the capital of the Indonesian province of Southeast Sulawesi. It is located on mainly the karst hills region with high rainfall and there were numerous human activities on the karst hills. Many landslides have occurred in these areas. Natural and human factors may contribute to the landslide. The purpose of this study was to determine whether the present GIS map of landslide-prone areas was in agreement or compatible when compared to the actual site conditions in Kendari City. This research is mainly a regional survey. Data was collected through direct interview and observation at the sites. Data were analyzed quantitatively with percentages. The results showed that 87.4% of the area in Kendari City as shown in the map of landslide-prone distribution using GIS was included in the low risk or slightly vulnerable category. The category of landslide-prone areas was divided into; Very low risk, Low, Medium, High risk and Very high risk which represents the less vulnerable areas to the very vulnerable areas. The level of compatibility of landslide-prone maps in Kendari City, when compared with actual site conditions, reaches 75%. This shows that the map of the GIS spatial analysis can be used as a guide in mapping the level of landslide vulnerability in Kendari City. Landslide-prone map may be used as a guideline for engineers, designers, planners, and city officials in planning to reduce the risk of potential disaster.